Gene regulatory network and epigenetic reprogramming of pig primordial germ cells - Zhang, Haixin (2016)
Primordial germ cells (PGC) are the precursors of the gametes. The mechanisms of PGC induction, specification and development are very well characterized in rodents, however recent investigations have demonstrated that the mechanisms of germ cell development differ significantly between mice and humans. Since the knowledge of PGC development in non-rodents is very limited, and early human embryos cannot be accessed it is important to establish a new model for PGC development with relevance to humans. In this thesis, I use pig embryo as a model for investigating PGC development in non-rodent mammals. The expression profile of key transcription factors, epigenetic reprograming and the role of signalling pathways were investigated during specification and development of pig PGCs. The key findings are: A- Specification of porcine PGC occurs after the onset of gastrulation, requiring BMP4 signalling. B- WNT signalling is required for the generation of precursors competent for germline commitment; however it is downregulated after PGCs are specified. WNT downregulation could be modulated by SOX17, the earliest gene expressed in pig PGCs. C- Epigenetic reprogramming of DNA and histone marks starts in pre-migratory porcine PGC. Furthermore, chromatin dynamics in pig gonadal PGCs resemble that of humans but differs to that of mice. D- The expression profile of transcription factors of porcine PGC is similar to that of humans, but different to mouse PGC. In conclusion, this study has highlighted critical differences between mice and humans/pigs during germ cell specification. I provide evidence that the pig embryo is a useful model for the study of human development, and future studies will need to be directed to re-evaluate concepts of cell differentiation and early lineage commitment established in mice that may not apply to humans.